1989
DOI: 10.2143/ast.19.2.2014909
|View full text |Cite
|
Sign up to set email alerts
|

A Generalization of Automobile Insurance Rating Models: The Negative Binomial Distribution with a Regression Component

Abstract: The objective of this paper is to provide an extension of well-known models of tarification in automobile insurance. The analysis begins by introducing a regression component in the Poisson model in order to use all available information in the estimation of the distribution. In a second step, a random variable is included in the regression component of the Poisson model and a negative binomial model with a regression component is derived. We then present our main contribution by proposing a bonus-malus system… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
73
0
5

Year Published

1992
1992
2023
2023

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 131 publications
(78 citation statements)
references
References 10 publications
0
73
0
5
Order By: Relevance
“…These pure premiums can further assist the insurer to investigate financial adequacy. While it will be more appealing to examine the claims within a longitudinal context, for example, Dionne and Vanasse (1989), Pinquet et al (2001), Bolancé et al (2003), and Pinquet (1997Pinquet ( , 1998, we leave this for future work. Comprehensive reviews of statistical models for experience rating in insurance can be found in Pinquet (2000) and Gouriéroux and Jasiak (2007).…”
Section: Background and Motivationmentioning
confidence: 99%
“…These pure premiums can further assist the insurer to investigate financial adequacy. While it will be more appealing to examine the claims within a longitudinal context, for example, Dionne and Vanasse (1989), Pinquet et al (2001), Bolancé et al (2003), and Pinquet (1997Pinquet ( , 1998, we leave this for future work. Comprehensive reviews of statistical models for experience rating in insurance can be found in Pinquet (2000) and Gouriéroux and Jasiak (2007).…”
Section: Background and Motivationmentioning
confidence: 99%
“…then the mixture will result in a NB distribution with probability distribution: 1920; for extensions designed to include exogenous data and an application to accident data, see Lawless, 1987;and Dionne and Vanasse, 1989). The second equality in ( …”
Section: Basic Distributionsmentioning
confidence: 99%
“…The regression coefficients and the serial correlation parameters can be estimated via a method of moments approach such as generalized estimating equations. This is the approach used by Dionne and Vanasse (1989) and Pinquet and co-authors. 2.…”
Section: Literature On Dynamic Count Modelsmentioning
confidence: 99%
“…Within the actuarial literature, Dionne and Vanasse (1989) led applications by applying a random effects Poisson count model to automobile insurance claims. Here, a (time-constant) latent variable was used to represent heterogeneity among claims, which implicitly also induces a constant correlation over time.…”
Section: Introductionmentioning
confidence: 99%